Grieving students: The response and support of educators in Irish schools - MCGUCKIN, CONOR; O'BRIEN, AOIFE MARY (My University, 2014)
It is estimated that bereavement has affected between 36,000 and 60,000 young people in Ireland. Little academic research has been conducted to ascertain the response of Irish schools to bereavement and grief support. The research outlined in this paper documents the approach and response of Irish primary and post-primary schools regarding policy and provision of support to students who have experienced bereavement as well as providing preliminary analyses of exploratory interviews with key stakeholders. The Bereavement Audit Survey was administered to a representative sample of primary and post-primary schools throughout the Republic of Ireland (N = 1,474). A total of 372 questionnaires were returned (achieved rate of 25.24%). The results demonstrate that in the absence of clear advice and support, Irish schools are being proactive and supportive of the students in their care, however, they also indicate the desire for further support in terms of policy, curricula materials, practice direction, staff support, and a Continual Professional Development programme. Preliminary results from exploratory interviews with key stakeholders with a remit in the area of bereavement and loss support are indicative of a need for current resources to be utilised in a more effective manner to increase confidence, governmental support, and training.
PUBLISHED
Keywords: young people; students; grief; education; Bereavement